Using hypobaric oxygen techniques and hyperbaric intervention to level the playing field in olympic distance triathlon: Literature review and study proposal - Cedaro, R. L. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
It is the purpose of this discussion to briefly review some of the more recent scientific research, pilot and case studies in the areas of hypobaric oxygen techniques and hyperbaric interventions to ascertain their potential worth as legal performance enhancing practices as we head towards the new millenium. This presentation will also outline an applied research study to be conducted at the Runaway Bay Sports Super Centre (Gold Coast, Queensland) within the next 6-12 months, to ascertain the practical, tangible, measurable performance and physiological benefits and responses to these practices.